PROBLEM ABOUT THE DYSGRAFIA IN FRAMES OF THE PARADIGMA SPECIFIC LEARNING DISABILITIES - Jivko Jekov; Stanislava Pavlova (Peytchinski Publishing, 2004)
Disgraphy as a disturbance of the written form of speech is one of the common forms of speech pathology with students of the primary grades. It often leads to difficulties in gaining new knowledge and skills, and impedes the successful end of training process. For that reason it is of prime importance for the logopedic theory and practice to define and separate its symptoms, to separate it as independent nosology unit or being part of other distrubances.